1907 Ala. Laws 80 - (:unkn) unknown (My University, 1907)
Prohibiting selling or bartering any pistol of less than twenty-four inches in length of barrel or any brass knucks, metallic knucks, dirks, slungshot, Bowie knives, or knife of like kind. Violators fined not less than one hundred nor more than one thousand dollars, and perhaps also sentenced to hard labor not less than one nor more than three months.
Keywords: TRANSFER